Development of the economic mechanism for managing the resources of railway transport enterprises - Соколова, Л. В. (PC Technology Center, 2020)
The object of research is resource management of railway transport enterprises. One of the most problematic areas is the development of a mechanism for managing the resources of enterprises, taking into account the characteristics of individual indicators of their activities. The resource management process is implemented on the principle of «deviation management». The analysis of modern theoretical and methodological approaches to ensuring the management process of railway transport enterprises is carried out. Certain shortcomings of existing approaches to enterprise resource management are identified, taking into account their industry specifics, shortcomings in managing their activities in a competitive environment. In the course of the study, the approaches to modeling the process of resource management of railway transport enterprises were used. It has been determined that the theoretical basis for the formation of a resource management mechanism for railway transport enterprises is a theoretical research platform, which is a set of basic interrelated terminological concepts and categories. An important component of the enterprise resource management mechanism is the unit for assessing the integral indicator of the resource management efficiency of railway transport enterprises. The peculiarities of the synthesized mathematical model for assessing the integral indicator is the use of temporal local indicators of stimulants and destimulants, which reflect the dynamics of changes in the aggregate of both well-known and specific for industry enterprises indicators of the effectiveness of managing various types of resources of railway enterprises. Thanks to this, it is possible to analyze the dynamics of the numerical values of the desired indicator, which makes it possible to evaluate its trend over time -– a positive (with growth) or negative (with a decrease) trend of change. A critical examination of the data obtained will provide management with important exclusive information, the use of which will contribute to increasing the level of scientific validity of decisions taken at the stage of strategic planning, when drawing up business plans for the development of railway enterprises.
Розробка економічного механізму управління ресурсами підприємств залізничного транспорту
DOI: https://doi.org/10.15587/2706-5448.2020.215091
Keywords: trend watching; deviation management; mathematical model for assessing the integral indicator; theoretical platform